Strategi Peningkatan Employee Engagement Dosen Generasi Z di Perguruan Tinggi Indonesia - Rizky Nurhakiim; Lindawati Kartika; Indra Sembiring (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
Higher education in Indonesia is currently facing challenges in meeting the demand for academic staff due to the increasing number of lecturers approaching retirement, while student enrollment continues to grow. This situation highlights the urgent need for lecturer regeneration, with Generation Z emerging as a potential group that brings distinct characteristics and work expectations compared to previous generations. This study aims to enhance the engagement of Gen Z lecturers as a strategy to retain young talent and make an optimal contribution to the sustainability of higher education. The methods employed are Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis and the Analytical Hierarchy Process (AHP). The findings indicate that the most influential factor is career growth opportunity, with university leadership identified as the key actor, and the top strategic goal being to increase retention and reduce turnover. The most effective strategy identified is the Adaptive Career Acceleration Program. Keywords: Employee Engagement; Generation Z; Higher Education; Lecturer; SWOT-AHP